A study of Hamka's concept of virtue based on his selected works - Noramira bt Adnan @Jamaluddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study aims to explore the concept of virtue in the thought of the great Indonesian Muslim scholar Haji Abd Malik Karim Amrullah (1908-1981) or better known as HAMKA. This study focuses on HAMKA's concept of virtue from the point of view of Islam. HAMKA's discussion on virtue relates to the discussion on duty and responsibility, therefore this study also highlights his ideas on the duties and responsibilities of selected professions. The method adopted by this study is library research. Using descriptive and analytical methods from HAMKA's selected works along with other works concerning the issue of virtue in Islam, this research seeks to formulate HAMKA's concept of virtue. The findings indicate that HAMKA's concept of virtue is based on reason and revelation. He states that canying out moral and religious duties requires purification of the human soul through the application of the ethics of taw(1id and the Prophetic teaching. HAMKA considers the virtues of love and moderation as the major virtues from which four major virtues are derived. Furthermore, the concept of moderation is fundamental to his concept of virtue. He emphasizes moderation in all aspects of human life and regards a moderate person as a virtuous person. His concept of virtue involves both individual and social dimensions. Moreover, the framework of HAMKA's concept of virtue is closely tied to the concept of duty and responsibility through which virtue is put to the test. In advocating the concept of viJ:tue, HAMKA relies heavily on the works of great Muslim scholars of the past like Miskawayh, al-GhazaU, al-RazI and others. It is true that HAMKA's conceptions of virtues were influenced by the Platonic idea but, he follows the footstep of great Muslim scholars who were very vigilant and analytical prior to accepting any" information or knowledge from outside Islamic sources. They have evaluated, modified and constructed those concepts in accordance with the worldview, ethical principles, ethical values and norms of Islam; which is known as integration and relevantization in their systematic scheme of tajdid in the process of Islamicization of the human knowledge.